A Study of the Mechanism of the Congruence of Leader–Follower Power Distance Orientation on Employees’ Task Performance - Bao, Yan; Liao, Shudi; Liao, Jianqiao; Zhang, Yucheng; Deng, Chuanjun; Guo, Zhiwen (Frontiers in Psychology, 2019)
Based on implicit leadership theory, we examine the congruence effect of leader-follower power distance orientation on follower trust in a supervisor and work engagement, which in turn influences employees’ task performance. Results of Polynomial regressions on 526 dyads supported the congruence effect hypothesis. The results show that (1) the congruence of leader-follower power distance orientation leads to better performance; (2) under the condition of congruence, Subordinate task performance is higher when leader-follower power distance orientation matching in low-low ratings congruence than it is in high-high ratings congruence; (3) under the condition of asymmetrical incongruence, the follower had higher task performance when a leader’s power distance orientation is lower than a follower’s power distance orientation; (4) trust in supervisor and the work engagement mediates the effect of congruence of leader-follower power distance orientation on employees’ task performance; (5) trust in supervisor also mediates the effect of congruence of leader-follower power distance orientation on employees’ work engagement.